A New Method to Synthesise the Sinusoidal Oscillator Based on Series Negative Resistance-Capacitance and its Implementation Using a Single Commercial IC, LT1228 - Worawut Kulapong; Winai Jaikla; Surapong Siripongdee; Roman Sotner; Peerawut Suwanjan; Amornchai Chaichana (My University, 2023)
An alternative method for synthesising the sinusoidal oscillator based on series negative resistance-capacitance is presented in this paper. The proposed topology is constructed with the series negative resistance-capacitance circuit connected in parallel with a grounded resistor and capacitor. To validate the proposed method, a new grounded series negative resistance-capacitance simulator is also proposed as a subcircuit for synthesising the sinusoidal oscillator. The series negative resistance-capacitance simulator is based on a commercially available integrated circuit (IC), LT1228. The equivalent negative resistance and equivalent negative capacitance can be adjusted electronically using an external DC bias current. The sinusoidal oscillator that is synthesised using the proposed method consists of a single LT1228, two capacitors, and three resistors. The frequency and the condition of the oscillation are orthogonally adjusted. Also, the condition of oscillation is electronically controlled. The amplitude of the sinusoidal waveform is adjustable. In addition, the output voltage node of the proposed oscillator has a low impedance, which allows it to connect to other circuits without using an additional buffer. Both PSPICE simulation and experiment are used to validate the proposed circuits.
Keywords: Equivalent series resistance; Negative resistance; Oscillation (cell signaling); Sine wave; LCR meter; Radio Frequency Integrated Circuit Design